The Investigation Of Heat-Resistant PLA Produced By Additive Manufacturing Technology - Ficzere, Péter; Lukács, Norbert László (International Journal of Engineering and Management Sciences, 2020)
In recent years, additive manufacturing technologies have been increasingly used in both custom and small-series production. In such cases, the component must remain functional under realistic conditions.. This means that there must also has a load‑bearing capacity. In many cases, materials are already suitable for strength. However, in many cases (machine parts, outdoor use) the models need to operate reliably at higher temperatures. This seems to be solved by the most widespread additive manufacturing technology (FDM), with a new heat-resistant material, HT PLA. In many cases, the use of cooling is essential during manufacture, especially for parts with high overhangs where hardening of the material is required as soon as possible to achieve the correct surface quality. In this paper, we investigated the effect of cooling applied during manufacturing on the mechanical strength